Використання програмно-педагогічного засобу з дисципліни «Проектування програмного забезпечення» - Колмакова, В. О.; Шаров, Сергій Володимирович; Шаров, Сергей Владимирович; Sharov, Sergii; Курлянський, С. С. (My University, 2020)
UK: У статті повідомляється про розробку програмно-педагогічного засобу для персонального комп’ютера з дисципліни «Проектування програмного забезпечення». Виявлено, що впровадження інформаційно-комунікаційних технологій в освітню діяльність є закономірним процесом інформатизації освіти. Вони дозволяють забезпечити диференціацію навчання, сформувати індивідуальну освітню траєкторію здобувача освіти, сприяють розвитку творчої особистості. Проаналізовано напрямки та форми впровадження інформаційно-комунікаційних технологій в освіті. Зазначається, що професія IT-спеціаліста вважається однією з найбільш затребуваних спеціальностей, причому попит на неї постійно зростає. Програміст повинен володіти фаховими компетентностями з розробки та проектування програмного забезпечення, баз даних тощо. У статті здійснюється огляд функціональних можливостей програмно-педагогічного засобу, який стане у нагоді під час самостійної роботи з дисципліни «Проектування програмного забезпечення». До структури програмного продукту відноситься блок лекцій, лабораторні роботи, модуль тестування, блок навчальних електронних тренажерів. Описуються основні функціональні блоки програмно-педагогічного засобу та етапи роботи з ними. RU: Сообщается про разработку программно-педагогического средства для персонального компьютера по дис-циплине «Проектирование программного обеспечения». Выявлено, что внедрение информационно-коммуникационных технологий в образовательную деятельность является закономерным процессом информа-тизации образования. Они позволяют обеспечить дифференциацию обучения, сформировать индивидуальную образовательную траекторию студента, способствуют развитию творческой личности. Проанализированы на-правления и формы внедрения информационно-коммуникационных технологий в образовании. Отмечается, что профессия IT-специалиста считается одной из самых востребованных специальностей, причем спрос на нее постоянно растет. Программист должен обладать профессиональными компетенциями по разработке и проек-тированию программного обеспечения, баз данных и тому подобное. В статье осуществляется обзор функцио-нальных возможностей программно-педагогического средства, который пригодится во время самостоятельной работы по дисциплине «Проектирование программного обеспечения». Структура программного продукта со-стоит из блока лекций, лабораторных работ, модуля тестирования, блока учебных электронных тренажеров. Описываются основные функциональные блоки программно-педагогического средства и этапы работы с ними. EN: Purpose. The article reports on the software and pedagogical tools’ development in «Software Engineering» discipline, it describes the software development stages, its functionality, the algorithm for operating with information blocks. Methodology. Analysis and synthesis of scientific and methodological literature on programming, software design, the discipline’s work program have been used to realize the purpose of the study and to determine the content of software and teaching aids. The method for observation of teachers and students has been used to define the specifics of teaching the discipline. Findings. It has been revealed that the information and communication technologies implementation in educational activities is a natural process of education informatization. Such technologies allow providing differentiation of training, individual educational trajectory formation, facilitate the development of the applicant’s creative personality. Directions and forms of information and communication technologies application in education have been analyzed. It has been found that distance learning systems, cloud and mobile technologies, electronic educational resources are being successfully implemented now. It has been noted that the IT-specialist profession, in particular software engineer, is considered one of the most popular specialties. The programmer must have professional competencies in the development and design of software and databases, etc. The developed software and pedagogical tool will improve the quality of higher education students’ independent work in the process of studying «Software Engineering» discipline. The structure of the software product includes a block of lectures, laboratory work, testing, a block of training electronic simulators and other components. Originality lies in the training simulators system application that will help to consolidate the acquired knowledge and master the discipline better. Practical value. The software and pedagogical tools are designed for higher education students studying «Software Engineering» discipline. Conclusions. The use of software and pedagogical tools will allow students to work independently in «Software Engineering» discipline and to form appropriate professional competencies of future programmers.
Использование программно-педагогического средства по дисциплине «Проектирование программного обеспечения»
Use of software and pedagogical tools in «Software engineering» discipline
Keywords: навчання; освіта; програміст; програма; проектування; забезпечення; обучение; программист; программа; проектирование; обеспечение; study; education; programmer; program; engineering; software